Spermatozoa morphometry and ultrastructure in estuarine crocodile (Crocodylus porosus) - Wan Nor Fitri; Haron, Wahid; Tengku Rinalfi Putra; Raj, Dana; Yawah, Donny; Latip, Qayyum; Ab Aziz, Abdul Malek (Wolters Kluwer - Medknow Publications and Media, 2020)
Objective: To evaluate normal spermatozoa morphometry and ultrastructure in estuarine crocodile (Crocodylus porosus).